1991
DOI: 10.1002/ar.1092300103
|View full text |Cite
|
Sign up to set email alerts
|

On the question of a subdural space

Abstract: The structure of the meninges, with particular attention to the architecture of the inner portions of the dura mater and the arachnoid mater, has been reviewed in reference to the probable existence of a "subdural" space. The dura is composed of fibroblasts and large amounts of extracellular collagen. The innermost part of the dura is formed by the dural border cell layer. This layer is characterized by flattened cells with sinuous processes, extracellular spaces containing an amorphous material, and the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 45 publications
4
119
0
4
Order By: Relevance
“…In contrast, no leptomeningeal localization of Tn-C was detected ( Figure 2D). The Tn-X+ trabecula might correspond to the leptomeninges trabecula in the subarachnoid space (Haines, 1991;Imura and Sato, 2008). These observations in monkeys were similar to those of our previous findings of Tn-X localization in mouse CP of lateral ventricles and 228 K. Imura and I. Sato leptomeninges (Imura and Sato, 2008).…”
Section: Resultssupporting
confidence: 89%
“…In contrast, no leptomeningeal localization of Tn-C was detected ( Figure 2D). The Tn-X+ trabecula might correspond to the leptomeninges trabecula in the subarachnoid space (Haines, 1991;Imura and Sato, 2008). These observations in monkeys were similar to those of our previous findings of Tn-X localization in mouse CP of lateral ventricles and 228 K. Imura and I. Sato leptomeninges (Imura and Sato, 2008).…”
Section: Resultssupporting
confidence: 89%
“…The inner or meningeal dura has greater numbers of fibroblasts and proportionally less collagen. 1,2) The venous sinuses are located at points where the meningeal dura is reflected off the periosteal dura to form the meningeal reflection. In the present case, the diagnosis of interdural hematoma was confirmed by histological examination, which demonstrated that the hematoma was located between the two layers of the meningeal dura.…”
Section: Discussionmentioning
confidence: 99%
“…Frederickson found that the number of cells varied with location and were consistent with the dural border cells described by Nabeshima et al 13 Haines described periosteal and meningeal dural layers. 17 Modified fibroblasts with no organized junctional complexes were seen beneath the meningeal layer. This layer in the normal state was continuous externally with the dura and internally with the arachnoid with no subdural space.…”
Section: Subdural Hematoma Anatomymentioning
confidence: 99%